2009
DOI: 10.1524/ract.2009.1615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dose rate on the radiolytic stability of a BTBP solvent for actinide(III)/lanthanide(III) separation

Abstract: Irradiation / Dose rate / Solvent extraction / Partitioning / Actinides / Lanthanides / Distribution ratio / Separation factorSummary. The recently developed ligand MF2-BTBP dissolved in cyclohexanone is a promising solvent for the group separation of trivalent actinides(III) from the lanthanides(III). Its high stability against nitric acid has been demonstrated recently. Since the solvent is also exposed to a continuously high radiation level in the counter current process, the radiolytic stability of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that poly-aromatic nitrogen compounds, N-PAHs, acting as tetradentate chelating ligands to the metal ions in the extraction, have the ability to sufficiently separate An(III) from Ln(III). [7][8][9][10] One of these N-PAHs, 6,6'-bis (5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol [1,2,4]triazin-3-yl) [2,2]bipyridine, CyMe4-BTBP (Figure 1), has promising process potential, [11][12][13][14][15][16] as it has proven to be resistant towards acidic environments [17][18][19] and strong radiation from radioactive decomposition 13,20 Qualitative reasoning concerning the Lewis basicity of the extractant and the somewhat softer character of the actinoid(III) ions compared to the lanthanoid(III) ones has been used to explain the An(III)/Ln(III) separation capacity of N-PAH ligands. 32,33 An(III)/Ln(III) separation by CyMe4-BTBP has also been observed to vary with the solvent used.…”
Section: Introductionmentioning
confidence: 99%
“…The tert-butyl-substituted derivative 2 [12] (Figure 1) posesses a higher solubility than CyMe 4 -BTBP 1 in suitable diluents such as 1-octanol and cyclohexanone, [13] although its solvent extraction kinetics are slower than those of 1. More recently, a symmetrical BTP ligand derived from camphor has shown both improved solubility and fast extraction kinetics compared to related BTP ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Recently, it has been shown that the extraction properties of ligands such as 1 can be improved considerably if the ligand is pre-organized for metal binding with a phenanthroline moiety, which locks the ligand into the required cis conformation. [11] The tert-butyl-substituted derivative 2 [12] ( Figure 1) posesses a higher solubility than CyMe 4 -BTBP 1 in suitable diluents such as 1-octanol and cyclohexanone, [13] although its solvent extraction kinetics are slower than those of 1. More recently, a symmetrical BTP ligand derived from camphor has shown both improved solubility and fast extraction kinetics compared to related BTP ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that the use of varying J-dose-rates for the irradiation of 0.01 M 4-t-butyl-6,6'-bis (5,5,8,8,-tetramethyl-5,6,7,8-tetrahydro-benzo[1,2,4]triazin-3-yl)-bypyridine (MF2-BTBP) in cyclohexanone resulted in different effects on D Am and D Eu (Fermvik et al 2009). The solvent extraction efficiency of americium and europium was unchanged when the solutions were irradiated at 15 Gy h -1 , while distribution ratios decreased to about 60% of their initial value when the solutions were irradiated to the same absorbed dose at 1.2 kGy h -1 .…”
Section: Dose Rate Effectsmentioning
confidence: 99%